أحكام إنتقال الملكية العقارية المثقلة بتأمين عيني - مراد, سلطاني (جامعة الوادي.University eloued, 2021)
"تناولنا في هذه الدراسة نظام الترقية باعتباره أهم المواضيع التي تهم فئة الموظفين العموميين كل مهتم بقطاع الوظيفة العامة، فالتسيير العقلاني للموارد البشرية في الوقت الحالي يتطلب وجود نظام فعّال للحوافز على غرار الترقية، لأنها تحقق للموظف جملة من الامتيازات المادية والمعنوية وتحقق في نفس الوقت للجهاز الإداري الأهداف التي وضعت من أجلها بما يرفع من مستوى العمل بفاعلية و كفاءة. حيث تطرقنا في الفصل الأول إلى الإطار المفاهيمي للترقية ، تناولنا فيه مفهوم الترقية وأهميتها وأهدافها و أسسها و كذا أنواعها والتي من خلالها يتدرج الموظف في رتبته الأصلية و تسمى الترقية بالدرجة و يترتب عليها زيادة في راتب الموظف ومنها ما يتغير بها مركز الموظف في السلم الوظيفي وتسمى الترقية في الرتبة و الترقية في المجموعة والتي يترتب عليها زيادة في المسؤوليات، كما اشرنا إلى الشروط الواجب توفرها، ناهيك عن مشاكل وموانع الترقية أما الفصل الثاني تطرقنا فيه إلى دراسة حالة مديرية الحماية المدنية بالوادي كنموذج تطبيقي للترقية وعرجنا فيه عن الإجراءات المتبعة للترقية داخل هاته المؤسسة. ""In this study, we dealt with the promotion system as the most important topics of interest to the category of public servants, everyone interested in the public service sector. The rational management of human resources at the present time requires the existence of an effective system of incentives similar to promotion, because it achieves for the employee a set of material and moral privileges and at the same time achieves the administrative body The objectives for which it was set in order to raise the level of work effectively and efficiently. Where we discussed in the first chapter the conceptual framework for promotion, in which we discussed the concept of promotion, its importance, objectives, foundations and types, through which the employee is classified in his original rank, which is called promotion. According to the grade and entails an increase in the employee’s salary, including what changes the employee’s position in the career ladder called promotion in rank and promotion in the group, which necessitates an increase in responsibilities, as we have clarified the conditions to be fulfilled, and not to mention the problems and obstacles that prevent promotion. In the second chapter, we dealt with the case study of the Civil Protection Directorate in the Valley as an applied model for promotion, and we referred to the procedures followed for promotion within this institution. "
ماستر عقاري
Keywords: التأمينات العينية - الملكية العقارية-الشهر العقاري; In-kind insurances/real estate property-real estate -registration